DEVELOPMENT OF BIO-BASED PRESSURE-SENSITIVE ADHESIVE FORMULATIONS DERIVED FROM ROSIN ESTERS USING MIXTURE DESIGN METHODOLOGY - Mardiah Mardiah; Aqsha Aqsha; Tjokorde Walmiki Samadhi; Winny Wulandari; Antonius Indarto (Mulawarman University Press, 2026)
Pressure-sensitive adhesives (PSAs) are commonly used in medical, packaging and industrial applications. Nevertheless, conventional petroleum-based adhesives raise concerns about sustainability, environmental impact and dependence on non-renewable resources. The objective of this study was to synthesize an eco-friendly bio-based pressure-sensitive adhesive from rosin ester by using simplex lattice design (SLD) methodology. The adhesive formulation was comprised of glycerol rosin ester, polyethylene glycol (PEG) rosin ester, lecithin, polyvinyl alcohol (PVA) and borax as cross linking agent. Adhesive performance was evaluated by peel strength, holding power and cohesion analysis. The result indicated that formulations with greater concentrations of glycerol rosin ester showed better adhesive properties with peel strength 0.8 N/cm and holding power 800 s. The optimum formulation by SLD optimization was 9 parts glycerol rosin ester, 7 parts PEG rosin ester and 4 parts lecithin. The proposed bio-based adhesive has not yet exceeded the performance of acrylic-based pressure-sensitive adhesive. However, it demonstrated adequate performance for lightweight labeling. In addition, renewable rosin-based raw materials provide a sustainable option to petroleum-derived adhesives, reducing dependence on fossil resources and driving the growth of green adhesive materials.